Evolution of copper arsenate resistance for enhanced enargite bioleaching using the extreme thermoacidophile Metallosphaera sedula. (1st December 2017) - Ai, Chenbing; McCarthy, Samuel; Liang, Yuting; Rudrappa, Deepak; Qiu, Guanzhou; Blum, Paul
Abstract: Adaptive laboratory evolution (ALE) was employed to isolate arsenate and copper cross-resistant strains, from the copper-resistant M. sedula CuR1. The evolved strains, M. sedula ARS50-1 and M. sedula ARS50-2, contained 12 and 13 additional mutations, respectively, relative to M. sedula CuR1. Bioleaching capacity of a defined consortium (consisting of a naturally occurring strain and a genetically engineered copper sensitive strain) was increased by introduction of M. sedula ARS50-2, with 5.31 and 26.29% more copper recovered from enargite at a pulp density (PD) of 1 and 3% (w/v), respectively. M. sedula ARS50-2 arose as the predominant species and modulated the proportions of the other two strains after it had been introduced. Collectively, the higher Cu 2+ resistance trait of M. sedula ARS50-2 resulted in a modulated microbial community structure, and consolidating enargite bioleaching especially at elevated PD.